Advancing Graduate Limnology Education Through Active Learning and Community Partnerships: A Pilot Program at the Large Lakes Observatory. (24th July 2017) - Schreiner, Kathryn M.; Katsev, Sergei; Steinman, Byron; Sterner, Robert W.; Williams, Julia; Zak, Kevin
Abstract: At the Large Lakes Observatory at the University of Minnesota Duluth (UMD), we are addressing issues with an outdated limnology graduate curriclum by designing a flipped‐classroom, interdisciplinary limnology course sequence that incorporates partnerships with industry, meaningful field and analytical work, and integrated skills learning for our graduate students. This new curriculum is co‐taught by four instructors with different research backgrounds and is meant to teach students with a wide range of undergraduate preparation without significant time spent on in‐class review, or leaving anyone behind. The courses, which include lecture and practice classes each semester in the graduate students' first year, are built around a course website, www.studywater.org, which will go public in fall of 2018. Funded by the National Science Foundation Division of Graduate Education, this pilot program will provide a new interdisciplinary curriculum applicable to graduate limnology programs and a public website with limnology modules designed to be searchable and open to the public. Here, we describe in detail our new course sequence, including curriculum, industry partnerships, and field work with the students; provide information on the challenges we faced in developing and teaching this course; and our advice for overcoming those challenges.